Competitive strategy of a foreign multinational in Brazilian poultry production - Azevedo, Denise Barros de; da Silva Rengel, Liane Aparecida Aires; Malafaia, Guilherme Cunha; Thomé, Karim Marini (Revista de Administração da UFSM, 2012)
This paper addresses the question of the strategies involved in the import process of cages for laying hens, directed at the multinational enterprise distribution center. Identifies the reasons why a multinational company invests in Brazil, specifically in the city of Araraquara, São Paulo, where it is implementing a distribution center (DC). Developing the study of the strategies involved in the process, according to the main issue of the work, it took place through the exploratory analysis of the current logistics process of the Company, identifying the strategies adopted and the advantages of the new process. In order to achieve the objectives, the study is based on the theoretical study of Porter's five competitive forces, SWOT analysis, generic strategies adopted to achieve return on investment and, based on issues such as import , logistics, warehousing and distribution center. The survey shows that deployment of the DC, the strategy involves the insertion in the national market, specifically in São Paulo that is the biggest market of laying hens in the country to gain competitive advantage, and the multinational also adopts the strategy generic differentiation, with regard to technology and product quality. Despite the high costs of construction and maintenance of the DC, they represent a barrier to market entry, have no financial risk for the multinational enterprise, since this deployment will also increase the demand for the product, allowing the return on invested capital.